ANALISIS EFISIENSI PEMASARAN PRODUKSI JAGUNG DI KECAMATAN BANDAR SRIBHAWONO KABUPATEN LAMPUNG TIMUR - Asih Titiana; Ktut Murniati; Eka Kasymir (Lampung University, 2021)
This study aims to analyze the efficiency of corn marketing. The research method used is a survey method. Data collection was carried out in Bandar Sribhawono District of East Lampung Regency in January - March 2019. Farmer respondents were chosen randomly and marketing agency respondents were taken by following the marketing flow. Data used are primary and secondary data. The analysis method used is the S-C-P (Structure, Conduct, Performance) model. The results showed that the corn marketing system in Bandar Sribhawono Sub-district has not been efficient, because the market structure faced by farmers was the oligopsonistic market structure, market behavior shows that farmers are still disadvantaged and act as price takers, there was one marketing channel with producer share (PS) below 55%, high marketing margin and profit margin ratio (RPM) does not spread evenly. Key words: corn, efficiency, marketing